Community Empowerment in Kebanggan Village: Asset-Based Community-Driven Development (ABCD) Approach - Adinugraha, Hendri Hermawan; Al Masobih, Ikrom; Nafiyah, Ilma; Anas, Ahmad (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
The main objective of this service is to identify and describe the potential of Kebanggan Village from the Asset-Based Community-Driven Development (ABCD) approach. This service method uses the ABCD approach. The ABCD-based service method shows high flexibility and adaptability when facing local challenges and community dynamics in Kebanggan Village. By prioritizing existing assets and potentials, this method can adapt to the specific needs and conditions of Kebanggan Village, which in turn encourages the success of the overall empowerment program in Kebanggan Village. The results of community service in Kebanggan Village using the Asset-Based Community-Driven Development (ABCD) approach have successfully created significant positive changes in community empowerment in Kebanggan Village. This community service activity has proven to improve economic and social welfare and build a foundation for long-term sustainability through identifying and utilizing existing assets, capacity building, and institutional strengthening in Kebanggan Village. The implementation of this service demonstrates that with the right approach, the people of Kebanggan Village can become agents of change to develop their community. In the future, this initiative's sustainability and further development will largely depend on the joint commitment and strong partnership among all stakeholders in Kebanggan Village.